Glycogen Synthase Kinase 3β (GSK3β) Modulates Antiviral Activity of Zinc-finger Antiviral Protein (ZAP) - Sun, Lin (American Society for Biochemistry and Molecular Biology, 2012)
Zinc-finger antiviral protein (ZAP) is a host factor that specifically inhibits the replication of certain viruses, including HIV-1, Ebola virus, and Sindbis virus. ZAP binds directly to specific viral mRNAs and recruits cellular mRNA degradation machinery to degrade the target RNA. ZAP has also been suggested to repress translation of the target mRNA. In this study, we report that ZAP is phosphorylated by glycogen synthase kinase 3β (GSK3β). GSK3β sequentially phosphorylated Ser-270, Ser-266, Ser-262, and Ser-257 of rat ZAP. Inhibition of GSK3β by inhibitor SB216763 or down-regulation of GSK3β by RNAi reduced the antiviral activity of ZAP. These results indicate that phosphorylation of ZAP by GSK3β modulates ZAP activity.